گاریباڵدی و یەكگرتنی ئیتالیا ١٨٠٧/١٨٧٠ - نجم, خسرو عبدالرحیم (Sulaimani Journal for Humanities, 2023)
The history of the political and military struggle can be considered for Giuseppe Garibaldi and Italy as a successful experiment of those peoples and nations whose lands are dispersed and did not achieve national political unity in the nineteenth century. It is clear to historians that Kurdistan was ruled by a number of princes who were not able to form a united Kurdistan or a Kurdish confederation that brings together all the emirates within the framework of a federal system in the nineteenth century and during the years of the Garibaldi revolution in Italy. Problems of local interests, lack of joint ventures, influence of religion, lack of charismatic leaders and weak nationalist ideology prevented them from doing so. Garibaldi was not a cleric with the status of a Kurdish sheikh, prince, or cult leader. Garibaldi grew up at a time when his country was ruled by several princes, kingdoms and local authorities. At the same time, Austrian occupation and French military and religious domination were prevailed. Garibaldi overcame power and local interests and led his people and country toward unity. In Italy and during Garibaldi's reign, there was no such thing as panchristianism, such as political Islam, which confused the Kurds and drove them out through nationalism and national interests. In Garibaldi's experiment, national consciousness and national interests overcame religion, and Garibaldi and the Italians won the bet. This research provides a step-by-step overview of the historical process and aims to fill a gap in Kurdish history with this valuable experience. Garibaldi proved to be a global revolutionary and even in Latin America he supported the independence and freedom of the peoples of those regions.